Fibril Network Strategy Enables High‐Performance Semitransparent Organic Solar Cells - Xie, Yuanpeng; Cai, Yunhao; Zhu, Lei; Xia, Ruoxi; Ye, Linglong; Feng, Xiang; Yip, Hin‐Lap; Liu, Feng; Lu, Guanghao; Tan, Songting; Sun, Yanming (Advanced functional materials, 2020)
The development of semitransparent organic solar cells (ST‐OSCs) represents a significant step toward the commercialization of OSCs. However, the trade‐off between power conversion efficiency (PCE) and average visible transmittance (AVT) restricts further improvements of ST‐OSCs. Herein, it is demonstrated that a fibril network strategy can enable ST‐OSCs with a high PCE and AVT simultaneously. A wide‐bandgap polymer PBT1‐C‐2Cl that can self‐assemble into a fibril nanostructure is used as the donor and a near‐infrared small molecule Y6 is adopted as the acceptor. It is found that a tiny amount of PBT1‐C‐2Cl in the blend can form a high speed pathway for hole transport due to the well distributed fibril nanostructure, which increases the transmittance in the visible region. Meanwhile, the acceptor Y6 guarantees sufficient light absorption. Using this strategy, the optimized ST‐OSCs yield a high PCE of 9.1% with an AVT of over 40% and significant light utilization efficiency of 3.65% at donor/acceptor ratio of 0.25:1. This work demonstrates a simple and effective approach to realizing high PCE and AVT of ST‐OSCs simultaneously. A fibril network strategy is demonstrated to fabricate semitransparent organic solar cells (ST‐OSCs). An effective hole transport pathway can be maintained even when a small amount of PBT1‐C‐2Cl donor is incorporated in the blends due to the well distributed fibril nanostructure formed by PBT1‐C‐2Cl. A high efficiency of 9.1% with an average visible transmittance of over 40% is achieved for ST‐OSCs.